Carbon dots based FRET for the detection of DNA damage - Kudr, Jiri; Richtera, Lukas; Xhaxhiu, Kledi; Hynek, David; Heger, Zbynek; Zitka, Ondrej; Adam, Vojtech (Biosensors & bioelectronics, 2017)
Here, we aimed our attention at the synthesis of carbon dots (C-dots) with the ability to interact with DNA to suggest an approach for the detection of DNA damage. Primarily, C-dots modified with amine moieties were synthesized using the one-step microwave pyrolysis of citric acid in the presence of diethylenetriamine. The C-dots showed strong photoluminescence with a quantum yield of 4%. In addition, the C-dots (2.8±0.8nm) possessed a good colloidal stability and exhibited a positive surface charge (ζ=36mV) at a neutral pH. An interaction study of the C-dots and the DNA fragment of λ bacteriophage was performed, and the DNA binding resulted in changes to the photoluminescent and absorption properties of the C-dots. A binding of the C-dots to DNA was also observed as a change to DNA electrophoretic mobility and a decreased ability to intercalate ethidium bromide (EtBr). Moreover, the Förster (or fluorescence) resonance energy transfer (FRET) between the C-dots and EtBr was studied, in which the C-dots serve as an excitation energy donor and the EtBr serves as an acceptor. When DNA was damaged using ultraviolet (UV) radiation (λ=254nm) and hydroxyl radicals, the intensity of the emitted photoluminescence at 612nm significantly decreased. The concept was proved on analysis of the genomic DNA from PC-3 cells and DNA isolated from melanoma tissues.
Keywords: nádorové buněčné linie; DNA Damage; biosenzitivní techniky; ultrafialové záření; DNA; uhlík; Quantum Dots; lidé; poškození DNA; Fluorescence resonance energy transfer; Biosensing Techniques; Cell Line, Tumor; kvantové tečky; Quantum dots; luminiscenční látky; Carbon; rezonanční přenos fluorescenční energie; Humans; Biosensing; Fluorescence Resonance Energy Transfer; Ultraviolet Rays; UV irradiation; Luminescent Agents